2018
DOI: 10.9734/jeai/2018/41694
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics Physico-Chemical and Carbon Balance in Fluvic Entisol after Six Years Fertilization with Manure and Gliricidia

Abstract: Soils in the semi-arid region of northeastern Brazil have low natural fertility and therefore, plant growth and productivity can be adversely affected. The application of mineral fertilizers is economically unfeasible by farmers in this region. The use of organic inputs found in farms, such as animal manure and the biomass of gliricidia leaves and branches (Gliricidia sepium Jacq. Walp), is a viable and low-cost option. Thus, the objective of this study was to evaluate influence of organic fertilizations over … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…The agronomic efficacy of using Gliricidia sepium to formulate biofertilizers was reported by Alakhyar et al (2019), since these formulations are able to supply the needs of different crops and maintain the soil fertility, especially when associated with cattle manure (Garrido et al, 2017). Since this species is a leguminous plant able to fix atmospheric nitrogen in symbiosis with rhizobia, besides being tolerant to water stress and easy to propagate, it is considered an important alternative to provide greater autonomy to and reduce the costs of family farmers (Primo et al, 2018).…”
Section: Resultsmentioning
confidence: 99%
“…The agronomic efficacy of using Gliricidia sepium to formulate biofertilizers was reported by Alakhyar et al (2019), since these formulations are able to supply the needs of different crops and maintain the soil fertility, especially when associated with cattle manure (Garrido et al, 2017). Since this species is a leguminous plant able to fix atmospheric nitrogen in symbiosis with rhizobia, besides being tolerant to water stress and easy to propagate, it is considered an important alternative to provide greater autonomy to and reduce the costs of family farmers (Primo et al, 2018).…”
Section: Resultsmentioning
confidence: 99%
“…When studying Gliricidia and Leucaena alleys as a way to improve soil properties, Fernandes et al [27] found that the residues incorporated 160 and 130 kg ha −1 year −1 of N, respectively (when only considering N). The leguminous alleys recovered about 20% of N directly from the residues deposited in the soil [11][12][13][14][15][16]. BNF can also represent N inputs relevant to the soil/plant system and reduce the need for N fertilizer application, which is often expensive and most susceptible to losses [8].…”
Section: Macronutrient Leaf Contents and Productivitymentioning
confidence: 99%